Wet Bulb Globe Temperature: Indicating Extreme Heat Risk on a Global Grid. (20th February 2023) - Brimicombe, Chloe; Lo, Chun Hay Brian; Pappenberger, Florian; Di Napoli, Claudia; Maciel, Pedro; Quintino, Tiago; Cornforth, Rosalind; Cloke, Hannah L.
Abstract: The Wet Bulb Globe Temperature (WBGT) is an international standard heat index used by the health, industrial, sports, and climate sectors to assess thermal comfort during heat extremes. Observations of its components, the globe and the wet bulb temperature (WBT), are however sparse. Therefore WBGT is difficult to derive, making it common to rely on approximations, such as the ones developed by Liljegren et al. (2008, https://doi.org/10.1080/15459620802310770, W B G T L i l j e g r e n WBGT_Liljegren ) and by the American College of Sports Medicine ( W B G T A C S M 87 WBGT_ACSM87 ). In this study, a global data set is created by implementing an updated WBGT method using ECMWF ERA5 gridded meteorological variables and is evaluated against existing WBGT methods. The new method, W B G T B r i m i c o m b e WBGT_Brimicombe, uses globe temperature calculated using mean radiant temperature and is found to be accurate in comparison to W B G T L i l j e g r e n WBGT_Liljegren across three heatwave case studies. In addition, it is found that W B G T A C S M 87 WBGT_ACSM87 is not an adequate approximation of WBGT. Our new method is a candidate for a global forecasting early warning system. Plain Language Summary: The Wet Bulb Globe Temperature (WBGT) is an international standard for how we measure the effect of heat on the human body. It is used across sectors in health, industry, sports, and climate to calculate how we feel and how our body responds during heat extremes. Its calculation has historically relied on globe thermometer and wet bulb temperature observations, which are however not widely available. This has made WBGT difficult to calculate and meant approximations have been created. Here we formulate a new WBGT method that can be used with global gridded data that are freely available and we compare it against other methods in common use. We find that our method is accurate when compared to the existing gold standard WBGT method. Key Points: We create an accurate method for calculating Wet Bulb Globe Temperature (WBGT) using Mean Radiant Temperature termed WBGTBrimicombe It is found that WBGTamsc87 also known as WBGTsimple is not an accurate approximation of WBGT WBGTBrimicombe can assist with robust heat stress standards across sectors including in public and occupational health